2020
DOI: 10.1155/2020/6489159
|View full text |Cite
|
Sign up to set email alerts
|

Lemon Balm Extracts Prevent Breast Cancer Progression In Vitro and In Ovo on Chorioallantoic Membrane Assay

Abstract: Breast cancer is the most frequently diagnosed malignant pathology, representing the primary cause of cancer death in women. Natural products are an appealing strategy to limit the progression of the disease. Targeting angiogenesis in breast cancer may positively impact on poor prognosis of breast cancer. As source of natural compounds, we investigated the leaves of Melissa officinalis L. (MO), known as lemon balm, an aromatic plant that spontaneously grows in the South and Western areas of Romania, being trad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 63 publications
(84 reference statements)
0
26
0
Order By: Relevance
“…On the third day of incubation, a volume of 5–7 mL of albumen was extracted to allow the chorioallantoic membrane to detach from the eggshell so that the blood vessels could be more easily observed. On the fourth day of incubation, a window was cut in the upper part of the egg, which was then covered with adhesive tape, and the eggs were reintroduced into the incubator until the day the experiment began [ 28 , 29 ].…”
Section: Methodsmentioning
confidence: 99%
“…On the third day of incubation, a volume of 5–7 mL of albumen was extracted to allow the chorioallantoic membrane to detach from the eggshell so that the blood vessels could be more easily observed. On the fourth day of incubation, a window was cut in the upper part of the egg, which was then covered with adhesive tape, and the eggs were reintroduced into the incubator until the day the experiment began [ 28 , 29 ].…”
Section: Methodsmentioning
confidence: 99%
“…The supernatant was collected and submitted to LC-MS analysis. All polyphenols were separated on a reverse phase Zorbax Eclipse Plus C18 column (3.0 × 100 mm × 3.5 microns) by gradient elution with a mobile phase consisting of a mixture of 0.1% acetic acid and methanol as follows: 5% methanol up to 5 min, 42% methanol for 38 min, the same proportion up to 41 min and 5% methanol for 1 min as described before [16]. The LC-MS parameters were the following: injection volume, 10 µL; flow rate, 1 mL/min; column temperature, 40 • C; UV detection at 330 and 370 nm; MS detection by electrospray ionization (ESI) in the single ion monitoring mode (SIM); capillary voltage, 3500 V; dry gas flow, 12 L/min at 350 • C; nebulizer pressure, 55 psig; fragmentor 70.…”
Section: Identification Of Phenolic Compounds By Liquid Chromatography-mass Spectrometry (Lc-ms)mentioning
confidence: 99%
“…People frequently consume Melissa officinalis herbal tea to ensure a good digestion, to reduce gastrointestinal disorders, to avoid sleep disturbance and for its antispasmodic properties [9,10]. Furthermore, many research studies have shown that MO extract possesses promising antitumor potential in various human cancer cell lines [11][12][13][14][15][16]. Cancer, a highly aggressive and heterogenic disease, is considered one of the causes for the elevated mortality rates worldwide [17].…”
Section: Introductionmentioning
confidence: 99%
“…The critical moment is tumor-induced angiogenesis. Melissa officinalis leaf extract halted neovascularization in breast adenocarcinoma MDA-MB-231 cells [ 202 ]. Antiangiogenic effects were also exerted by Prunella vulgaris root extract in MCF-5 cells [ 150 ].…”
Section: The Lamiaceae Family Plantsmentioning
confidence: 99%